Implementation of Supervision of Regional Government Implementation Based on Government Regulation Number 12 of 2017 In Gowa District - Yusri Yunus; La Ode Husen; M. Kamal Hijaz (JURNAL HUKUM SEHASEN, 2024)
The objectives of this research are: 1) To know and analyze the implementation of the effectiveness of the implementation of supervision of regional government administration based on Government Regulation Number 12 of 2017 in Gowa Regency, and 2) To know and analyze the factors that influence the implementation of the effectiveness of the implementation of supervision of regional government administration based on Government Regulation Number 12 of 2017 in Gowa Regency. The research method, in this case, combines normative legal elements, which are then supported by the addition of data or empirical elements. This normative-empirical research method also concerns the implementation of normative legal provisions (laws) in action in every particular legal event that occurs in a society. The research results show that the implementation of supervision of regional government administration based on Government Regulation Number 12 of 2017 in Gowa Regency in terms of the scope of supervision is internal supervision carried out internally functionally. This means that supervision is carried out by officials within the organization itself functionally, whose position is part of the institution being supervised. Factors that influence the implementation of supervision of regional government administration based on Government Regulation Number 12 of 2017 in Gowa Regency include legal substance, legal structure, legal culture, legal knowledge facilities and infrastructure, and legal awareness.